A Comparison of Size, Shape, and Fractal Diversity Between Coral Rubble Sampled From Natural and Artificial Coastlines Around Okinawa Island, Japan - Masucci, Giovanni D.; Biondi, Piera; Reimer, James D. (Frontiers in Marine Science, 2021)
Substrate surface area and fractal complexity have been reported to influence the abundance and diversity of mobile cryptic animal communities. Surfaces with higher fractal dimensions not only offer additional space for colonization, but bias space availability toward smaller size ranges, increasing the number of available niches. Conversely, smaller surface areas tend to be associated with a decrease in abundances while reduced fractal complexities may support less diversity in the benthic community. In this study, we compared morphological parameters between rubble sampled from rubble mounds accumulated at the seaward side of artificial breakwaters and rubble sampled from a nearby location with no breakwaters (=control site). The purpose of this work was to establish a methodology for comparing the surface area and fractal complexity of coral rubble fragments using easily available equipment that could be efficiently utilized during field work. Rubble fragments were individually weighed and photographed in controlled light conditions. Each photograph was then analyzed using ImageJ software. Rubble pieces from each photograph went through segmentation, the separation of sample outlines from the picture background, before being measured and analyzed for surface area, width, and length (size estimators), and circularity, aspect ratio, roundness, solidity, and Feret properties (shape estimators). Surface fractal complexity was also measured, using the box counting method on segmented rubble surfaces. We observed lowered surface areas, weight, and fractal complexity for rubble fragments sampled at the breakwater. We demonstrate how this method could be used to compare coral rubble from a variety of environmental conditions, thus becoming a useful aid in environmental monitoring, in addition to adding important information to the collection and analyses of biological data.